The design of an inner-motile waste-energy-driven piezoelectric catalytic system. (13th April 2021) - Peng, Fengping; Xu, Wanxin; Hu, Yunya; Fu, Weijie; Li, Haozhen; Lin, Jingyuan; Xiao, Yafeng; Wu, Zhe; Wang, Wei; Lu, Chunhua
Abstract : A kind of waste-energy-driven catalytic system was explored for the first time using magnetically actuated artificial cilia. Abstract : Inspired by microorganisms in nature, a new type of waste-energy-driven catalytic film was explored for the first time using magnetically actuated artificial cilia. Due to its singular characteristic ciliary movement, the inner-motile catalytic film is capable of capturing waste mechanical energy from flows, which can unexpectedly drive electrochemical reactions in solutions. Based on this, the piezoelectric deposition of Ag nanoparticles was achieved for the first time, which makes Ag nanoparticles distribute more evenly on the body of ZnO nanowires, enhancing the catalytic performance dramatically. Moreover, the influence of Ag nanoparticles on the piezoelectric catalysis was also detected, which can boost the deeper understanding of the piezo-catalytic mechanism. In summary, the inner-motile strategy facilitates the realization of waste-energy-driven catalytic technology, providing a new working prototype for driving the piezo-chemical reaction.